2017
DOI: 10.1016/j.artd.2017.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Relative impact of hospital and surgeon procedure volumes on primary total hip arthroplasty revision: a nationwide cohort study in France

Abstract: BackgroundBoth surgeon and hospital procedure volumes have been found to be associated with total hip arthroplasty (THA) outcomes. However, little research has been conducted on the relative influence. We studied the association between THA survivorship and both hospital and surgeon procedure volumes, considering their relative impact.MethodsA population-based cohort included all patients aged ≥40 years having received a unilateral primary THA from 2010 to 2011, from the French National Health Insurance Databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 47 publications
1
8
1
Order By: Relevance
“…The cumulative PJI incidence at our hospital was 1.1% which is comparable with reports from other centres with high operative volume 21213. Various studies have shown that increase in the hospital operative volume results in fewer postoperative complications 1415. In addition, ultra-clean operating rooms, dedicated personnel, and improved surgical techniques contribute to the low incidence of PJI observed at our hospital.…”
Section: Discussionsupporting
confidence: 82%
“…The cumulative PJI incidence at our hospital was 1.1% which is comparable with reports from other centres with high operative volume 21213. Various studies have shown that increase in the hospital operative volume results in fewer postoperative complications 1415. In addition, ultra-clean operating rooms, dedicated personnel, and improved surgical techniques contribute to the low incidence of PJI observed at our hospital.…”
Section: Discussionsupporting
confidence: 82%
“…Our study overcomes a few methodological limitations of previous research and shows that, nowadays in Catalonia, the volume of THA and TKA procedures performed in a hospital per year could be related to the incidence of revision. Contrary to previous research focused on other contexts carried out using unmatched cohorts [6,7,12,13,14], higher-volume hospitals could have a higher risk of revision in their primary prostheses than lower-volume centers in Catalonia.…”
Section: Discussioncontrasting
confidence: 60%
“…In the lower-volume hospitals in Catalonia, usually only one surgeon performs each type of arthroplasty. Due to this, despite the lower volume by hospital, the volume by surgeon could be high, a factor that has been related to lower revision rates [13,14,22]. Further research using matched cohorts from different healthcare contexts, e.g., using data from different countries’ or cultures’ registers, using different cut-off values to divide between higher- and lower-volume groups, and accounting for surgeon and hospital-environment related variables, could help improve our understanding of how volume by year is related to the incidence of revision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, there may be selection bias in our study because complex dysplasia cases are more likely to be performed by higher-volume and fellowship-trained surgeons. As surgeon volume and arthroplasty fellowship training are associated with lower complication rates, lower operative times, and improved outcomes [28][29][30][31][32][33][34][35][36], this would bias the dysplasia group to trend towards improved outcomes in comparison with the general OA cohort. Surgeon volume and fellowship training are not available via the NSQIP database which prevented stratification of this potential effect.…”
Section: Discussionmentioning
confidence: 99%